Improving boiler operation without additional capital investment - Mustafa, Azeman (Faculty of Chemical & Natural Resources Engineering, 1994)
Boiler is the most widely - used combustion equipment as a steam generator in most of the energy intensive industries in Malaysia. As the cost of generating energy steadily increases, there is a need to operate a boiler properly so that the maximum amount of energy could be generated. In addition to that, less harmful polluting species discharged from the boiler could be achieved as nowadays there is an increasing concern of the environment degradation due to the inefficient operation of the combustion equipment. This paper gives a brief review on the simple and yet important practices that can be used to optimize the efficiency of the boiler performance without additional capital investment.